Justice and mercy : ethical minimum: legal and moral (Prudentia Iuris, 2017)
The text delves into the indispensable character of law as a minimum ethical, enabling a properly human coexistence, it also intends to facilitate the optimizing want inseparable from the morality. Or, to quote the terms of the Bull of Convocation of the Extraordinary Jubilee of Mercy: justice is undoubtedly “the first necessary and indispensable step”, without forgetting that “the Church nevertheless needs to go further to reach a higher and most significant finishing line”. Alludes, in some of the footnotes, to suggestions from the author that lend themselves to maintain the dialogue to which the document invites.
Keywords: Justice; Mercy; Minimum ethical; Moral